Flexible Carbon Fiber/SnO2@rGO Electrode with Long Cyclability for Lithium-Ion Batteries - Wenjie Zhang; Yongqi Liu; Zhouyang Qin; Lingxiao Yu; Jiabiao Lian; Zhanliang Tao; Zheng-Hong Huang (Batteries)
Flexible electrodes are highly desirable for next-generation wearable lithium-ion batteries. To achieve high-capacity flexible electrode materials, SnO2 with high theoretical capacity has been introduced into electrodes and shows promising capacity. However, the electrodes are still confronted with major challenges in terms of inferior rate capability and cycling stability, which are caused by large volume changes of SnO2 during the lithiation/delithiation process. Here, we adopt an adsorption assembly strategy to fabricate a flexible carbon fiber/SnO2@rGO electrode that effectively stabilizes the volume changes of SnO2 and enhances the charge transport kinetics in electrodes. The sandwich-like structure endows the electrode’s high flexibility and succeeds in improving both rate capability and cycling stability. The flexible carbon fiber/SnO2@rGO electrode delivers a high capacity of 453 mAh g−1 at 50 mA g−1 and outstanding capacity retention of 88% after 1000 cycles at 2 A g−1.